Characterization of radiative recombination in Ag(In,Ga)Se2 thin films by photoluminescence - X. F. Zhang; J. Liu; G. F. Liu (AIP Advances, 2016)
A detailed analysis of the radiative recombination processes in Ag(InGa)Se2 thin films grown by a three-stage method was carried out by photoluminescence. The temperature and excitation dependence of the photoluminescence spectra was used to identify the recombination types and determine the ionization energy of the defects in the films. Significant differences were observed between the spectra of the Ag-rich and Ag-poor samples. The Ag-rich films were dominated by two emission peaks of donor acceptor pairs (DAPs). The DAP at lower energy level is attributed to recombination of donor level 13.8 meV (Agi) with acceptor level 70.3 meV (AgIn), while the one at high energy level is assigned to recombination of donor level 18.5 meV (Agi) with acceptor level 108.9 (AgSe). When Ag/III atomic ratio was near 2.00, a phonon related-structure began to appear, which is attributed to the phonon replica of the high energy level DAP. In the case of Ag-poor AIGS samples, the dominant broad asymmetric peaks of AIGS films with different Ag/III atomic ratios were related to potential fluctuation at low temperature, and the compensation level decreased with increasing Ag/III atomic ratio. The emission line was assigned to recombination of donor level 12.7 meV (Agi) with acceptor level 175 meV (